Between the centre and the periphery: The abolition of the death penalty in Portugal (1867) - Vaz, Maria João; Gonalves, Gonçalo (Rage Reckoning and Remedy - Global Meeting on Law and Society, 2022)
This paper aims to examine the reform of the Portuguese penal system during the ascension and consolidation of the Constitutional Monarchy in Portugal focusing in particularly on the abolition of the death penalty for civil crimes established in 1867. A working hypothesis is proposed: that it is only possible to fully understand penal reform in Portugal if we bring together the national context and the transnational circulation of punitive and penal models. The analysis of abolitionist movements, the opportunities, and meanings of the abolition of the death penalty in the legal systems of several states since the 19th century, has constituted a relevant line of research in several areas, including History. Thus in this paper we will look into the process of abolition of the death penalty in Portugal as an internal political and legal process, but also as a mark intended to an international ‘audience’. Studying the international reverberations of the abolition of the death penalty in Portugal and how they were ‘celebrated’ in the country is thus a key point to understand the multiple meanings of the abolition of the death penalty in Portugal. The period under analysis begins roughly with the first liberal revolution, in 1820, and finishes with the reactions to the “Sentencing and Prison Reform Act”, enacted on July 1, 1867, when the death penalty was abolished for civil crimes and established the penitentiary system in Portugal. The sources of the work will be various essays and studies, particularly those by jurists, published during this period, as well as the various political debates that will be surveyed and analysed. We will also examine the reactions in the foreign press (especially British, French, Spanish and Brazilian) to the abolition of the death penalty in Portugal.